Tilia saxatilis (Malvaceae), a new species from limestone areas of Guangxi, China - Zhao-Cen Lu; Shi-Li Chang; Ming-Lin Mo; You-Dong Wu; Wei-Bin Xu (PhytoKeys)
Tilia saxatilis Z.C.Lu & W.B.Xu, a new species was discovered in limestone areas of Guangxi, China. The morphology shows that T. saxatilis is similar to T. tuan Szyszyl., but differs by having leaf blades that are oblong or ovate-oblong, entire margins, fruit ellipsoid, 5-angled, apex acute.